ANALISIS HADIS-HADIS BAHAN AJAR PAI SEKOLAH MENENGAH PERTAMA - Malkan, Mardhiya Agustina; Jannah, Raudhatul (UIN Antasari Banjarmasin, 2023)
The purpose of this study is to describe the ethical values contained in the hadiths in the teaching materials of PAI class VII in Junior High School. Where in the face of the era of disruption with the condition of massive innovation in various things into life, causing the unpreparedness of the younger generation to deal with it, especially in the context of national life with the conditions of multicultural Indonesia. Behavioral shifts also change along with technological advances. Ethics education is an important part of the concept of human life in order to create harmony. This type of research is a literature research by studying and examining library materials related to the traditions studied, namely through the steps of mentakhrij hadith and tracing the syarah as well as tracing its content from various references, and then analyzing and concluding the ethical values contained therein. The result of this research is that there are eight ethical points contained in 5 hadiths, namely: mutual respect, preventing discrimination, discipline, patience, obedience, humility, generosity and forgiveness. The results of this study can be used as material in the reconstruction of millennial youth ethics education. Keywords: Ethics Education; Millennial Youth; Era of Disruption; Hadith Abstrak Tujuan penelitian ini adalah untuk mendeskripsikan nilai-nilai etika yang terdapat dalam hadis-hadis pada bahan ajar mata pelajaran PAI kelas VII di Sekolah Menengah Pertama dalam menghadapi era disrupsi dengan kondisi terjadinya inovasi besar-besaran dalam berbagai hal ke dalam kehidupan, menyebabkan ketidaksiapan generasi muda untuk menghadapinya, khususnya dalam konteks kehidupan kebangsaan dengan kondisi Indonesia yang multibudaya. Pergeseran perilaku turut berubah beriringan dengan kemajuan teknologi. Pendidikan etika menjadi bagian penting dari konsep kehidupan manusia agar tercipta keharmonisan. Jenis penelitian ini adalah penelitian pustaka dengan mempelajari dan menelaah bahan pustaka yang berhubungan dengan hadis-hadis yang diteliti, yaitu melalui langkah mentakhrij hadis dan menelusuri syarahnya serta menelusuri kandungannya dari berbagai referensi, dan kemudian menganalisis dan menyimpulkan nilai etika yang terdapat di dalamnya. Hasil dari penelitian ini adalah ditemukan delapan butir etika yang terkandung dalam 5 hadis yaitu: saling menghormati, mencegah diskriminasi, disiplin, sabar, patuh, merendah, pemurah dan pemaaf. Hasil penelitian ini dapat dijadikan bahan dalam rekonstruksi pendidikan etika remaja milenial. Kata Kunci: Pendidikan Etika; Remaja Milenial; Era Disrupsi; Hadis